Sistem Informasi Layanan Pernikahan Berbasis Web Pada Kantor Urusan Agama Mendahara Ilir Tanjung Jabung Timur - Farista R, Rahul; Sharipuddin, Sharipuddin (LPPM Universitas Dinamika Bangsa, 2023)
A web-based marriage service information system at the religious affairs office of Mendahara Ilir, Tanjung Jabung Timur, an institution that serves marriage registration. The process of marriage services in data collection at the Office of Religious Affairs is currently still being recorded manually by officers. This study aims to analyze and design a marriage service information system at the Mendahara Ilir religious affairs office, Tanjung Jabung Timur. The method used in this study is the waterfall method, the design of this information system produces a prototype using the Unified Modeling Language programming language, the information system designed can facilitate the process of inputting marriage data where the data will be stored in the same database so that the data from the marriage report can be well integrated. The information system created is only limited to the service information system for Marriage Schedule, Marriage Implementation, Marriage Book Publisher and Marriage Book Duplicate.